RANCANG BANGUN APLIKASI SMART CARD INTERFACE - Agus Swastika, I Putu; Pua Luka, Siti Saibah; Dwi Ananda, Yanno (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2012)
Opportunity to development smart card -based application is quite large as the need for smart card technology in various fields of both business and government agencies and BUMN. One brand that is widely used smart card is a smart card type from a vendor production NFC ACR122U ACS (Advanced Card System Limited) because prices are relatively affordable, but fairly tough. At the Thesis is done, the ACS (Advanced Card System Limited) as a manufacturer of smart card vendor type ACR122U NFC only supports several programming languages for development, among other Borland Delphi 7, Java, Microsoft Visual Basic 6.0, Microsoft Visual Basic.NET 2005, Microsoft .2005 Visual C #, Microsoft Visual C + + 6.0 Microsoft Visual C + + 2005. And what about other programming languages?, It will certainly be an obstacle for smart card application developers to develop applications based NFC smart cards 122U ACR, especially for developers who owned the programming language competence beyond the programming language that supported the current ACR NFC 122U. Constraints are primarily compatibility as well as the development time will be relatively longer. For that application development interface between a PC with Smart Card is flexible, able to communicate the smart card, smart card reader with the application to be developed with various programming languages (multiprogramming) that differ will help ease in the development of other applications based on smart ACR card 122U.
Keywords: smart card, smart card reader, ACR 122U, interfaces, multiprogramming.